Education in the balance mapping the global dynamics of school leadership - Wilkins, Raphael (Bloomsbury, 2014)
"Education in the Balance explores the significant choices and opportunities for the future development of schools and school systems internationally, including case studies in Pakistan and India, Colombia, Saudi Arabia and China. It draws attention to the increasing reliance on the judgements of leaders in a wide range of settings: schools, private companies and NGOs to choose options which, cumulatively, will have profound implications for the future of education. What knowledge, skills and attributes will these new leaders of education need, and how can they be developed? Raphael Wilkins maps out these issues, drawing on his extensive first had experience as an international consultant in education leadership"--Provided by publisher.